2019
DOI: 10.1016/j.apergo.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seating on the discomfort caused by mechanical shocks: Measurement and prediction of SEAT values

Abstract: Highlights  SEAT values indicate the influence of seats on vibration discomfort  SEAT values appear useful for both vibration and mechanical shock  SEAT values can be measured subjectively or objectively or predicted by a model  Low frequency high magnitude shocks merit further investigation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 23 publications
5
24
1
Order By: Relevance
“…Gong et al 16 and Ciloglu et al 18 used the SEAT value as an objective indicator to evaluate the vibration isolation efficiency of train seats and airplane seats, respectively. Patelli et al 19 through the study of two different thickness foam cushion found that with vertical mechanical shocks at low, medium, and high magnitudes (0.5, 1.0, and 2.0 ms À1.75 VDV) at frequencies between 1.0 and 16 Hz, the measured SEAT values were similar to the subjective SEAT values, the measured SEAT value was a good indicator of the effect of the seat on the discomfort. The above studies show that the SEAT value is a proper indicator for the research of the seat comfort, but a clear and consistent conclusion on the relationship between the SEAT value and the foam physical parameters has not yet been achieved.…”
Section: Introductionmentioning
confidence: 78%
“…Gong et al 16 and Ciloglu et al 18 used the SEAT value as an objective indicator to evaluate the vibration isolation efficiency of train seats and airplane seats, respectively. Patelli et al 19 through the study of two different thickness foam cushion found that with vertical mechanical shocks at low, medium, and high magnitudes (0.5, 1.0, and 2.0 ms À1.75 VDV) at frequencies between 1.0 and 16 Hz, the measured SEAT values were similar to the subjective SEAT values, the measured SEAT value was a good indicator of the effect of the seat on the discomfort. The above studies show that the SEAT value is a proper indicator for the research of the seat comfort, but a clear and consistent conclusion on the relationship between the SEAT value and the foam physical parameters has not yet been achieved.…”
Section: Introductionmentioning
confidence: 78%
“…The vertical displacement of the suspension mass above the front and rear wheels, the displacement at the center of mass of the car body, and the pitch angle are related as follows [26]:…”
Section: Analysis Of Influence Of Vehicle Motion On Cameramentioning
confidence: 99%
“…Train seats are crucial to decrease vibration transmission from the floor to the user. Together, the seat and human body constitute a coupled complex dynamic system [14,[21][22][23]. A significant discrepancy can be observed when comparing the transmissibility of subjects with identical characteristics, including identical mass.…”
Section: Introductionmentioning
confidence: 99%